THE EFFECT OF THINK PAIR SQUARE TO VII CLASS STUDENTS’ SCIENCE PROCESS SKILL - Indah Wigati; Dini Afriansyah; Aldiana Mabrukah (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This study aims to determine whether the learning model cooperative learning type thinking pair square affect the skills of science process students of VII class. This research uses quasi experiment method (quasi experimental ) research design with the matching only pretest-posttest control group design . Sampling by saturation sampling . The research sample is VII.1 class as control class and VII.2 class as experiment class. The instrument used in this study is a question in the form of multiple choice and essay, observation sheets science process skills of students and teacher observation sheet activities regarding adherence to the type of learning model cooperative learning Think Pair Square. The results of this study indicate that there are differences in the science process skills between students who follow cooperative learning model type think pair square with conventional learning model (discussion, lecture or question and answer) on the subject of the characteristics organism on VII class junior high school shown by hypothesis testing . The results of statistical calculations obtained t-arithmetic = 5.375 and t-table of 1.676 with dk (degrees of freedom) of 50 at a significant level of 5% so t-arithmetic > t-table that is 5.375> 1.676 . Based on the results of hypothesis testing, it can be concluded that the influence of think pair square model on the skills of students' science processes in the experimental class on the subject of the characteristics of organism on students in VII class in junior high school. Keywords: cooperative learning, characteristics of organism, TPS (Think Pair Square), process skills